Haemoprotozoa in wild short‐beaked echidnas (Tachyglossus aculeatus). Issue 3 (2nd November 2021) - Hill, AG; Boyd, SP; Clark, NJ; Proboste, T
Abstract : The occurrence and clinical significance of the protozoal parasite reported as Hepatozoon tachyglossi in wild short‐beaked echidnas ( Tachyglossis aculeatus ) have long been uncertain, as has its potential as a prognostic indicator. This retrospective survey of free‐ranging short‐beaked echidnas admitted to a wildlife hospital used morphological evidence to identify a H. tachyglossi prevalence of 56%, with parasitaemias affecting 0%–36% of monocytes. There was no statistical association between H. tachyglossi intensity and clinical status (P ‐ value = 0.12; 95% confidence interval = 0.1 to 1.3), nor between the presence of H. tachyglossi and age, reason for admission, outcome, season or location. Piroplasms, presumed to be Theileria tachyglossi, were concurrently identified in the erythrocytes of 88% of short‐beaked echidnas with no association between age, outcome, season or location, but a statistical association with the location where the animal was found (either on a road, airport runway, exposed urban area, or entangled). Given the current results, intracellular parasitism due to H. tachyglossi may be considered as an incidental finding on haematologic examination of short‐beaked echidnas and is likely not an effective prognostic indicator. Further research using molecular tools is required to resolve the uncertain identity of H. tachyglossi which has been based on morphologic characteristics alone.